Is the duration of dual antiplatelet therapy (DAPT) excessive in post-angioplasty in chronic coronary syndrome? Data from the France-PCI registry (2014–2019) - Mezier, A.; Motreff, P.; Clerc, J. M.; Bar, O.; Deballon, R.; Demicheli, T.; Dechery, T.; Souteyrand, G.; Py, A.; Lhoest, N.; Lhermusier, T.; Honton, B.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background while the duration of dual antiplatelet therapy (DAPT) following coronary angioplasty for chronic coronary syndrome (CCS) recommended by the European Society of Cardiology has decreased over the last decade, little is known about the adherence to those guidelines in clinical practice in France. Aim To analyze the real duration of DAPT post coronary angioplasty in CCS, as well as the factors affecting this duration. Methods Between 2014 and 2019, 8.836 percutaneous coronary interventions for CCS from the France-PCI registry were evaluated, with 1 year follow up, after exclusion of patients receiving oral anticoagulants, procedures performed within one year of an acute coronary syndrome, and repeat angioplasty. Results Post-percutaneous coronary intervention (PCI) DAPT duration was > 12 months for 53.1% of patients treated for CCS; 30.5% had a DAPT between 7 and 12 months, and 16.4% a DAPT ≤ 6 months. Patients with L-DAPT (>12 months) were at higher ischemic risk [25.0% of DAPT score ≥2 vs. 18.8% DAPT score ≥2 in S&I-DAPT group (≤12 months)]. The most commonly used P2Y12 inhibitor was clopidogrel (82.2%). The prescription of ticagrelor increased over the period. Conclusions post-PCI DAPT duration in CCS was higher than international recommendations in the France PCI registry between 2014 and 2019. More than half of the angioplasty performed for CCS are followed by a DAPT > 12 months. Ischemic risk assessment influences the duration of DAPT. This risk is probably overestimated nowadays, leading to a prolongation of DAPT beyond the recommended durations, thus increasing the bleeding risk.